Effect of Compactness by Timber Operations on the Infiltration Rate in a Sal Plantation - Ram, Nirmal; Patel, Sheelwant; Gupta, M. P. (Indian Forester, 1993)
The study was undertaken under Shorea robusta plantation in the foot-hills of Darjeeling Himalayas to observe the effect of timber operations on infiltration rate of the soil. The result revealed that due to movement of heavy trucks and dumping effects of heavy logs brings about a great compaction of the forest soil, in the timber operation site. Due to compaction of the forest floor, a reduction of soil porosity by more than 60% was noticed. There was also reduction in moisture-holding capacity due to disturbances. Initial (within five minutes) infiltration rate under undisturbed forest and disturbed forest by timber operation was 45.48 and 9.92 cm/hr respectively. Whereas it was 4.14 and 1.74 cm/hr at the end of a period of three hours. Accumulated infiltration in three hours was 36.05 and 7.64 cm in the undisturbed and disturbed site. The finding reveals that undisturbed sal forest having thick litter on its surface is much capable of intaking water. An efficient management should include guideline for avoiding heavy loads and retention of litter on forest floor for better soil and water conservation.